Magnus Haavelsrud, Education in Developments, Volume 3 (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
Review of Magnus Haavelsrud, Education in Developments. Volume 3 (Oslo: Arena, 2020). (ISBN 9788291040103) $4.99 and Paperback (ISBN 978-82-91040-09-7) $10.99.